Revisiting the dark figure. A microeconometric analysis of the under-reporting of property crime and its implications - MacDonald, Ziggy (The British journal of criminology, 2001)
In this paper we use data from the 1994 and 1996 British Crime Survey (BCS) to examine the under-reporting of property crime. Using bivariate probit analysis (corrected for sample selection), we find a strong association between factors influenced by the economic cycle and individuals' reporting inclinations. However, we find little evidence to connect reporting to individual criminality, but some association between individual attitudes to the police and the probability of reporting an incident. In general, individuals who are not in the labour market are much less likely to report property crimes compared to individuals who are in work, especially those who suffer some financial loss as a consequence of the crime. These findings have implications for economic models of crime that make use of official statistics. Where previously the dark figure' of hidden crime has been assumed to vary randomly through time, our results suggest that a large component of hidden crime varies systematically with the economic cycle. The implication of this is that economic models of crime should be corrected to allow for this relationship